Genetic variability of Rhizoctonia spp. isolated from different hosts and locations - Rashed, Osamah Zaid Ali; Abdullah, Siti Nor Akmar; Alsultan, Wael M. K.; Ahmad, Khairulmazmi (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Rhizoctonia species is well known as a destructive fungal pathogen in various agro-ecosystems globally. The current study attempted to investigate the genetic diversity among various anastomosis groups of Rhizoctonia species obtained from different locations and crops. Two types of markers were used to detect the genetic variability among isolates. The results showed that all the molecular markers were able to show reasonable polymorphisms. The clustering tree and PCA plot analysis supported the separation based on taxonomic groups more than the separation according to geographical origin and host. This indicates that there are other important factors that contribute to the genetic variation among Rhizoctonia isolates. The knowledge gathered in this study would be useful for developing crops that are resistant to Rhizoctonia diseases. This will assist in planning for the right crop rotation and proper disease management programs.